Design To Minimize Time Production For Reduce Energy Consumption On Jacquard Punching Machine Based On Green Manufacturing Method (study Case : Buana Intan Gemilang Corporation) - Firza Ahmad Setiyansyah; Haris Rachmat; Tatang Mulyana (eProceedings of Engineering, 2017)
Abstract In the 21st century, the use of machine energy in the industrial world has increased significantly every year. In 2000 the use of electric energy in the world around 13,000 Kwh and in 2015 has reached 22,000 Kwh. In Indonesia energy use by the industrial sector is also quite large, one of them is the textile industry sector. PT. Buana Intan Gemilang is a textile company that produces prayer mats and curtains with a wide sales area. PT. Buana Intan Gemilang has problem in making pattern card by using punching machine, energy use in punching machine is quite big because production process on punching machine using manual process. So it requires an improvement on the use of energy and production time of making pattern card. Green manufacturing is a method that can be used to solve problems associated with waste in the punching machine. The application of green manufacturing method is done in three stages; Identify your color, prepare your brush, paint it green, keep it green. After applying the green manufacturing method on PT. Buana Intan Gemilang energy usage of punching machine was reduced from 33116 Kwh to 8366 Kwh in producing one type of pattern card. Production time also increased in producing one type of pattern from 332 seconds to 83 seconds. Keywords: Green Manufacturing, Automation, Energy consumption, Production time, Punching machine